Public Health Risk in Animal Shelters - Voss, Kelly (My University, 2019)
Animal shelters play a critical role in society and their utility need not be argued. Sheltering community animals serves many purposes, of which many relate to public health. Keeping free-roaming animals off the roads, minimizing human encounters with dangerous animals, and providing people with healthy, adoptable animal companions are amongst a few of the ways animal shelters contribute to improving public health. However, animal shelters also present inherent risks to those who visit the shelter. Infectious diseases are of particular concern in animal shelters because group housing creates an environment of increased exposure, susceptibility, and transmission of disease (Pesavento & Murphy, 2014). Of the infectious diseases animal shelters commonly see, many are zoonotic and place people in contact with these animals at risk of disease. Other public health risks at animal shelters include animal-related injuries and personal safety. Animal shelters should consider these risks when managing their daily operations to maximize both animal and human health.
Keywords: public health; animal shelters; zoonotic